Bilateral consecutive choroidal neovascularization in Best vitelliform macular dystrophy. Issue 4 (9th June 2022) - Hoyek, Sandra; Lin, Lisa Y.; Kozek, Lindsay Klofas; Gonzalez, Efren; Rajabi, Farrah; Patel, Nimesh A.
Abstract: Best vitelliform macular dystrophy (BVMD) is a slowly progressive macular disease caused by a pathogenic variant of the Bestrophin ( BEST1 ) gene. Examination coupled with multimodal imaging and genetic testing are used to guide diagnosis and treatment. A 12-year-old girl was examined for decreased vision in the left eye and showed bilateral "egg-yolk"–like macular lesions with choroidal neovascularization (CNV) in the left eye. Six months later, she experienced decreased vision with appearance of CNV on optical coherence tomography angiography in the right eye. Injections of anti-vascular endothelial growth factor helped restore vision from 20/125 to 20/20 in the right eye with stabilization of her left eye (vision 20/40). Genetic testing revealed c.851A > G (p.Tyr284Cys), a heterozygous variant of the BEST1 gene. The same variant was found in her father, who was initially misdiagnosed with toxoplasmosis due to a peripheral retinal lesion in the left eye. This is the first report of bilateral consecutive CNV secondary to BVMD. Additionally, it highlights the likely pathogenic role of a novel variant of the BEST1 gene.